Fecal incontinence in irritable bowel syndrome: Prevalence and associated factors in Swedish and American patients. Issue 2 (31st August 2016) - Simrén, M.; Palsson, O. S.; Heymen, S.; Bajor, A.; Törnblom, H.; Whitehead, W. E.
Abstract: Background: Fecal incontinence (FI) is a prevalent but poorly recognized problem in the general population with profound negative effects on daily life. The prevalence of FI in irritable bowel syndrome (IBS) and its association with clinical, demographic, and pathophysiological factors remain largely unknown. Methods: One US (n=304) and one Swedish (n=168) patient cohort fulfilling Rome III criteria for IBS completed Rome III diagnostic questions on FI and IBS symptoms, and questionnaires on IBS symptom severity, quality of life, anxiety and depression, and work productivity impairment. The patients also underwent assessments of colorectal sensitivity and motility. Key Results: Fecal incontinence ≥ one day per month was reported by 19.7% (USA) and 13.7% (Sweden) of IBS patients. These proportions rose to 43.4% and 29.8% if patients with less frequent FI were included. Fecal incontinence prevalence was higher in older age groups, with a clear increase above age 40. Irritable bowel syndrome patients with FI reported greater overall IBS symptom severity, more frequent and loose stools, and greater urgency. Negative effects of FI on quality of life, psychological distress, and work productivity were demonstrated. No associations were found between colorectal physiology and FI. Conclusions & Inferences: Fecal incontinence is common in IBS patients, and similar to previous general population reports, the major risk factors for FI in IBS are older age, rectal urgency, and loose, frequent stools. When IBS patients have comorbid FI, the impact on quality of life, psychological symptoms, and work impairment appears greater. Abstract : We studied one US (n=304) and one Swedish IBS cohort (n=168), and fecal incontinence (FI) ≥ one day per month was reported by 19.7% (USA) and 13.7% (Sweden) of IBS patients.FI was associated with loose, frequent stools, urgency, and adverse impact on quality of life, psychological symptoms, and work productivity.